2014
DOI: 10.1007/s11356-014-3719-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of biochars on sorption and biodegradation of polycyclic aromatic hydrocarbons in soils—a review

Abstract: Amending polycyclic aromatic hydrocarbon (PAH)-contaminated soils with biochar may be cheaper and environmentally friendly than other forms of organic materials. This has led to numerous studies on the use of biochar to either bind or stimulate the microbial degradation of organic compounds in soils. However, very little or no attention have been paid to the fact that biochars can give simultaneous impact on PAH fate processes, such as volatilization, sorption and biodegradation. In this review, we raised and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 193 publications
5
43
0
Order By: Relevance
“…This is the main reason responsible for the CS350 and CS450 having greater S (TE) enrichment relative to the CS650. In the case of the CEC, results obtained in this study followed the same trend as S (TE) enrichment, whereby the CS450 had the greatest CEC (18.52 cmol kg À1 ) > CS350 (13.12 cmol kg À1 ) > CS650 (9.73 cmol kg À1 ) (Table S4) (Anyika et al, 2015).…”
Section: Relationship Between Production Temperatures Ste Enrichmentsupporting
confidence: 67%
See 2 more Smart Citations
“…This is the main reason responsible for the CS350 and CS450 having greater S (TE) enrichment relative to the CS650. In the case of the CEC, results obtained in this study followed the same trend as S (TE) enrichment, whereby the CS450 had the greatest CEC (18.52 cmol kg À1 ) > CS350 (13.12 cmol kg À1 ) > CS650 (9.73 cmol kg À1 ) (Table S4) (Anyika et al, 2015).…”
Section: Relationship Between Production Temperatures Ste Enrichmentsupporting
confidence: 67%
“…Likewise, since the straits of Malacca, is a busy oil tanker route transporting crude oil from the South-East Asia, to western countries, as well a route for oil tankers transporting oil from the Middle East to the Far East Asian countries (Zakaria et al, 2001), an integrated waste management system can be envisioned whereby the CSB will be used to mitigate pollution arising from accidental oil spills, while at the same time providing sequestration for CO 2 emission, thereby mitigating the effects of climate change. Towards these ends, the disadvantages of AC over biochar are well documented (Anyika et al, 2015;Oleszczuk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also suggested that the increased nutrient contents, carbon availability, water retention and pH in acid soils caused by biochar addition could explain the increase of the microbial abundance in the biochar-amended soil (Lehmann et al, 2011). In their review, Anyika et al (2015) explained how biochars affect microbes and microbial activities in the soils and cited several reasons: i) the increase of shelters for microorganisms due to the presence of pores and high surface area, ii) the increase of the water-holding capacity and the oxygen and nutrient contents, iii) the modification of soil pH and iv) the source of carbon and energy.…”
Section: Soil Biological Propertiesmentioning
confidence: 99%
“…Oleszczuk et al (2012) studied two kinds of biochars (obtained with maize stover and paper mill waste) and observed a more significant influence of paper mill waste biochar than maize stover biochar on the reduction of freely dissolved PAHs. The probable mechanisms by which biochars can impact both sorption and biodegradation of PAHs in soils have been reviewed by Anyika et al (2015) who supposed that: i) the sorption of PAHs by biochars is the main mechanism affecting their fate, transport and biodegradation in soils and ii) desorption kinetics in soils seem to be slow due to the strong affinity of PAHs to biochars. According to these authors, PAHs and biochars can be linked by three processes: i) the pep interactions between the benzene rings of the PAHs and those of the biochars, ii) the sorption into the nanopores of biochars and iii) the rapid adsorption at lower PAH concentrations and the absorption at higher concentrations due to the attainment of maximum adsorption.…”
Section: Organic Pollutantsmentioning
confidence: 99%